Pengenalan Teknologi Augmented Reality Quiver-3d Coloring Pada Pembelajaran IPA Siklus Hidup Makhluk Hidup Di SDN 1 Karangtumaritis Haurgeulis Indramayu - Subkhi, Nur; Irmayanti, Amelia (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2024)
Education in Indonesia, especially at the elementary school level, requires an innovative approach to improve the quality of learning. Technological advances have undergone major changes and are moving towards digital education. Natural Sciences (IPA) is one of the most important subjects at the elementary school level. Student understanding is often hampered by the limited learning media available. The results of observations with direct observation show that there is no interesting learning media in science learning on the life cycle of living things. Augmented Reality (AR) technology can be a solution to overcome this problem. One AR application that is very suitable for use in elementary school learning is Quiver-3D Coloring. The purpose of this service is to introduce technology, raise learning motivation, and find out students' responses to the use of the Quiver-3D Coloring Augmented Reality media. The instruments used are motivation questionnaire sheets and student response questionnaire sheets. The target of the program is 4th grade students of UPTD SD Negeri Karangtumaritis, with 39 respondents. The results of the activity show that; 1) The implementation of the program "Introduction to Augmented Reality Quiver-3d Coloring Technology in Science Learning on the Life Cycle of Living Things at SDN 1 Karangtumaritis Haurgeulis Indramayu" has generally been carried out well (successfully) in accordance with the planned goals and targets; 2) The description of student motivation after learning with the Augmented Reality Quiver-3D Coloring application media on the life cycle of living things is included in the very high category with a motivation percentage of 85.07%; 3) The description of student responses to "science learning on the life cycle of living things" with the Augmented Reality Quiver-3D Coloring application generally responded well (positively) with a percentage of 95.90%; and 4) The description of student responses to "the use of the Augmented Reality Quiver-3D Coloring application media" in Science Learning on the life cycle of living things, generally responded well (positively) with a percentage of 95.90%.